Pengaruh Manajemen Sekuritas Aplikasi Terhadap Keputusan Pengguna dalam Pengambilan Keputusan Menggunakan Aplikasi Dana sebagai E-Wallet Pilihan dalam Mengimplementasikan Ekonomi Digital Berbasis Kedaulatan NKRI - Avrilia Ayunia Widyaningrum; Edy Soesanto; Rani Nur Azizah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The objective of this study is to assess the performance of the DANA application as an electronic wallet and analyse the effect of managing the application's securities on user decision-making when using the application in the setting of the digital economy based on the sovereignty of the Unitary State of the Republic of Indonesia (NKRI). The study method employed was a qualitative literature review. The data was acquired by consulting relevant scholarly publications on Google Scholar to thoroughly comprehend the advancement of knowledge about the subject matter and identify areas of research that require further exploration. The hypothesis analysis revealed a significant correlation between the advantages of the digital economy, the growth of the digital economy, and the factors affecting the utilisation of E-Wallets or Dana apps within the Homeland. The development of the digital economy enhanced a nation's ability to withstand challenges by promoting economic sovereignty, cybersecurity and inclusive economic growth. Various factors, including data security and the rise of the digital economy, affected the utilisation of Dana applications. In addition, these factors affected the execution of national values. Utilising the Dana application as a digital wallet strengthened the nation's economic sovereignty and enhanced well-being and financial inclusivity across all segments of Indonesian society. Hence, comprehending the security management of the application and users' perspective regarding it is crucial in affecting users' trust and their decision to embrace the Dana application as their preferred E-Wallet for supporting the NKRI sovereignty-based digital economy.